Non-Extraction Treatment of Skeletal Class II Adult Patient with Total Maxillary Arch Distalization - Cenk Doruk; Özkan Semih Çankaya; İhsan Sami Güvenç (Galenos Yayinevi, 2015)
In this case report, we present an extraction-prescribed Class II division 1 adult patient's non-extraction treatment by distalization of the total maxillary arch with miniscrews. The miniscrews were inserted into the mesial of the upper first molars roots as far as possible, and total arch distalization was started by a nitinol coil spring (200 g per side) extended from the miniscrew to a hook attached between the canine and lateral. The distalization amount was expected to be the distance between the miniscrew and the second premolar root per side. At the end of the treatment, 2 mm molar distalization with 3 degree tipping was achieved. Class II division I adult patients with moderate overjet can be treated without extraction using these mechanics.